Thermal Analysis of Cutting Force and Optimization of Process Parameters for Curved Rake Face Skiving Tools - Li, Jiawei; Gao, Yanan (International Journal of Mechanical and Electrical Engineering, 2025)
Power skiving is a highly efficient and high-precision gear machining method. During the power skiving process, the cutting force and cutting temperature exerted on the tool significantly influence its service life. Improper selection of process parameters can easily lead to rapid wear and failure of the skiving tool. Currently, the characteristics of cutting forces and thermal behavior in such machining processes remain unclear, lacking theoretical guidance for tool design and process parameter optimization. To address these issues, this study designed and developed a three-dimensional model of a curved rake face skiving tool. A finite element-based simulation model of the power skiving process was established to calculate the cutting force and cutting temperature data. The influence of key process parameters on the cutting performance was analyzed. A full factorial experimental approach was adopted to optimize the power skiving process parameters based on the mean and peak values of cutting force, as well as the mean value of cutting temperature. Through comprehensive analysis, the primary factors affecting the cutting force and cutting temperature in power skiving were identified.